An integrated stochastic-fuzzy method for supply chain leanness evaluation in Iranian automotive small and medium enterprises - Behrouzi, Farzad, 1981-; Wong, Kuan Yew, supervisor; Fakulti Kejuruteraan Mekanikal (2013)
Thesis (Ph.D (Kejuruteraan Mekanikal)) - Universiti Teknologi Malaysia, 2013